2015
DOI: 10.1007/s10973-015-4389-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and nonisothermal decomposition kinetics of La2(CO3)3·3.4H2O

Abstract: The single-phase La 2 (CO 3 ) 3 Á3.4H 2 O with the orthorhombic type was synthesized by hydrothermal method. The results characterized by XRD, FTIR and DTA-TG showed that the thermal decompositions of La 2 (CO 3 ) 3 Á3.4H 2 O below 1,273 K experience four steps, which involve a two-stage dehydration and formation of anhydrous La 2 (CO 3 ) 3 at first, and then the formation of La 2 O 2 CO 3 and La 2 O 3 , respectively. An additional intermediate product assigned to La 2 O(CO 3 ) 2 was observed in the third step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…To further substantiate this by Fouriertransform infrared spectroscopy (FTIR), the spectrum of SFGO-La 3+ showed additional absorption bands between 668 and 818 cm −1 , which correspond to the characteristic bands of hydrated lanthanum carbonate (Fig. 4D) (50,51). In particular, the band at 668 cm −1 is likely due to lattice vibrations of La─O (51).…”
Section: Membrane Characterizationmentioning
confidence: 87%
See 1 more Smart Citation
“…To further substantiate this by Fouriertransform infrared spectroscopy (FTIR), the spectrum of SFGO-La 3+ showed additional absorption bands between 668 and 818 cm −1 , which correspond to the characteristic bands of hydrated lanthanum carbonate (Fig. 4D) (50,51). In particular, the band at 668 cm −1 is likely due to lattice vibrations of La─O (51).…”
Section: Membrane Characterizationmentioning
confidence: 87%
“…4D) (50,51). In particular, the band at 668 cm −1 is likely due to lattice vibrations of La─O (51). In addition, band shifts and changes were observed after cross-linking with La 3+ .…”
Section: Membrane Characterizationmentioning
confidence: 90%
“…The geometric models, widely used in the kinetic analysis of thermal decomposition reactions [20][21][22][23][24][25], are based upon the processes of nucleation and growth of product nuclei by interface advance. It was suggested that more reliable data can be obtained from the kinetic study of single crystals compared to powdery samples [1].…”
Section: Introductionmentioning
confidence: 99%
“…Another feature is when T is close to T 0 , E value should be infinity. [27][28][29][30][31] is: Figure 4b shows the Friedman plots for the pure VO 2 at a = 0.5 around the T p . Two plots demonstrate nonlinear plots of similar shape.…”
Section: Resultsmentioning
confidence: 99%